Effects of different moments of inertia on neuromuscular performance in elite female soccer players during hip extension exercise to prevent hamstring asymmetries and injuries: A cross-sectional study - Pumarola, J.; Badiola-Zabala, A.; Solana-Tramunt, M. (Sports, 2025)
Background: High-intensity actions like accelerations and decelerations, often performed unilaterally, are crucial in elite female football but increase the risk of interlimb asymmetries and injury. Flywheel resistance training enhances eccentric strength, yet limited research has assessed how different inertial loads affect mechanical outputs in unilateral exercises. Purpose: This study investigated how two inertial loads (0.107 kg·m2 and 0.133 kg·m2) influence power, acceleration, speed, and asymmetry during unilateral hip extensions in elite female footballers. Methods: Eighteen professional players (27 ± 4 years, 59.9 ± 6.5 kg, 168.2 ± 6.3 cm, BMI 21.2 ± 1.8) completed unilateral hip extensions on a conical flywheel under both inertia conditions. A rotary encoder measured peak/average power, acceleration, speed, and eccentric-to-concentric (E:C) ratios. Bilateral asymmetries between dominant (DL) and non-dominant (NDL) limbs were assessed. Paired t-tests and Cohen`s d were used for analysis. Results: Higher inertia reduced peak and mean acceleration and speed (p < 0.001, d > 0.8). Eccentric peak power significantly increased in the NDL (p < 0.001, d = 3.952). E:C ratios remained stable. Conclusions: Greater inertial loads reduce movement velocity but increase eccentric output in the NDL, offering potential strategies to manage neuromuscular asymmetries in elite female football players.